الحقوق الاجتماعية للمرأة في اتفاقية سيداو وموقف السعودية منها : دراسة فقهية تحليلية - Khadijah Yahuza Ibrahim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research aims to study the CEDAW (Convention of the Elimination of all the Forms of Discrimination against Women) Convention and social rights of woman contained therein. It explores the extent to which the articles of the convention agreed or contravene the Islamic Law. In the same vein, it explains the Saudi Arabia standing point with this regard and how they practically implement the articles it contained. Some articles of the convention are consistent with the Islamic law, some contravene it whilst others are of neutral nature where Ijtihaad could be applied. Amongst the consistent articles with the Islamic Law are: the equality of men and women in custody and upbringing of children, women's entitlement of choosing nationality, education, employment and health care, as well as the ones calling for combating all forms of women trafficking and exploitation in prostitution, and granting women full freedom to choose a spouse and to be married only with their full consent. The articles contravening the Islamic Law include: articles calling for the abolition of Islamic laws which, in their view, constitute discrimination against women in addition to some articles related to marriage and family matters. As for the Saudi implementation of the convention, it is believed that they were commitment to the agreement as they change some of the laws to comply with the articles signed in the CEDAW convention. The researcher used inductive approach in extracting information and an analytical method where the researcher analysed the social rights of women's rights in the convention. A descriptive analytical method is also applied to analyse and describe the Saudi stance on this agreement. The study found significant results that Islam takes precedence over maintaining the dignity and rights of women and never failed in her protection, contrary, Islam deals with men and women fairly and granted each of them rights and duties that commensurate with their biological composition. The United Nations has successfully prospered in reducing discrimination against women through this convention, but it, sometimes, fails to put into consideration the individual differences between the men and women, which yielded the comparison between the two deemed unfair. Saudi Government has applied what is consistent with the Islamic law and neglected what opposed it; they have issued new laws and Royal Decrees to affirm the equality between the men and women, significant progress has been made, although failure is perceived in some particles.